Fatty Acid Data and Crop Surveys Indicate Sources of Red Sunflower Seed Weevil (Coleoptera: Curculionidae), Populations and Suggest Strategies for Management. Issue 1 (2nd December 2020) - Prasifka, Jarrad R; Ferguson, Beth; Anderson, James V
Abstract: The red sunflower seed weevil, Smicronyx fulvus L., is a univoltine seed-feeding pest of cultivated sunflower, Helianthus annuus L. Artificial infestations of S. fulvus onto sunflowers with traditional (<25% oleic acid), mid-oleic (55–75%), or high oleic (>80%) fatty acid profiles were used to test if fatty acids could be used as natural markers to estimate the proportion of weevils developing on oilseed sunflowers rather than wild Helianthus spp. and confection (non-oil) types. Oleic acid (%) in S. fulvus confirmed the fatty acid compositions of mature larvae and weevil adults reflected their diets, making primary (oleic or linoleic) fatty acids feasible as natural markers for this crop-insect combination. Oleic acid in wild S. fulvus populations in North Dakota suggests at least 84 and 90% of adults originated from mid-oleic or high oleic sunflower hybrids in 2017 and 2018, respectively. Surveys in 2017 ( n = 156 fields) and 2019 ( n = 120 fields) extended information provided by S. fulvus fatty acid data; no significant spatial patterns of S. fulvus damage were detected in samples, damage to oilseed sunflowers was greater than confection (non-oil) types, and the majority of damage occurred in ≈10% of surveyed fields. Combined, data suggest a few unmanaged or mismanaged oilseed sunflower fields are responsible for producing most S. fulvus in an area. Improved management seems possible with a combination of grower education and expanded use of non-insecticidal tactics, including cultural practices and S. fulvus -resistant hybrids.